ASTROCHEMISTRY OF STAR FORMATION - Wiebe, D. S.; Kochina, O. V. (Одеські астрономічні публікації, 2013)
Star formation is one of the key processes governing the evolution of the Universe. It is accompanied by significant transformations in the chemical composition and the physical state of the interstellar medium. Combining observations in infrared and radio bands, we obtain a wealth of observational data on the star formation both in continuum and spectral lines. These lines mostly belong to molecules, from simple diatomic species to complex organic compounds. However, interstellar molecules are not well- mixed with the bulk interstellar gas (molecular and atomic hydrogen) and possess a complex evolution of their own. Thus, a straightforward interpretation of observational data is seldom possible. One needs sophisticated chemical and physical models to decipher processes occurring in star-forming regions.